Enhancing Competitiveness of Creative Industries: SME in West Sumatra - Husni, Tafdil; Rahim, Rida; ., Desyetti; ., Yurniwati (International Journal of Engineering and Technology, 2018)
This research is conducted to identify the competitiveness of creative industries in West Sumatra based on market orientation, entrepreneurial orientation, and competitive advantage. Variables used in this research are competitiveness, market orientation, entrepreneurship orientation, and competitive advantage. The method of collecting primary data are obtained through questionnaires and guided interviews. The primary data used are from survey to small industries and secondary data are from Department of Industrial and Trade Cooperatives (Diskoperindag) and Department of Tourism of West Sumatra. Hypothesis is tested using Partial Least Square (PLS) method. The research found that the increase of competitiveness will be reached if the company has competitive advantage and the manager/owner of creative industry is entrepreneurial-oriented. This entrepreneurial orientation influence competitiveness directly or mediated by competitive advantage. Whereas, market orientation cannot create creative industryâ€™s competitiveness either directly or mediated by competitive advantage.Â